Listen NCERT Audio Books to boost your productivity and retention power by 2X.
Factorize:
Factorize:
Factorize:
Factorize:
Factorize:
Factorize:
Factorize:
Factorize:
Factorize:
Factorize:
Factorize:
Factorize:
Factorize:
If then
104 x 96 =?
207 x 193 =?
305 x 308 =?
The question consists of two statements, namely, Assertion (A) and Reason (R), Please select the correct answer.
Assertion (A) | Reason (R) |
If (x – 1) is a factor of then k = - 2 | If (x – a) is a factor of p(x), then p(a) = 0. |
The question consists of two statements, namely, Assertion (A) and Reason (R), Please select the correct answer.
Assertion (A) | Reason (R) |
If is divided by (x – a), then the remainder is 5a. | If p(x) is divided by (x – a), then the remainder is p(a). |
The question consists of two statements, namely, Assertion (A) and Reason (R), Please select the correct answer.
Assertion (A) | Reason (R) |
If (x – 2) is a factor of then | If p(x) is divided by (x – a), then the remainder is p(a). |
The question consists of two statements, namely, Assertion (A) and Reason (R), Please select the correct answer.
Assertion (A) | Reason (R) |
The value of is 10800. | If a + b + c = 0, then |
Match the following columns:
Column I | Column II |
(a) If p (x) = x^{3} – 2x^{2} + 3x + 1 is divided by (x + 1), then remainder = …… | (p) |
(b) If (2x – 1) is a factor of q (x) = x^{3} + 2x^{2} + 3x + k then k = …… | (q) 50 |
(c) The degree of the constant polynomial (-5) is = …… | (r) – 1 |
(d) When x^{51} + 51 is divided by (x + 1), the remainder is = …… | (s) 0 |
The correct answer is:
(a)-……., (b)-……., (c)-……., (d)-…….,
Match the following columns:
Column I | Column II |
(a) If p (x) = 81x^{4} + 54x^{3} - 9x^{2} – 3x + 2 is divided by (3x + 2), then remainder = …… | (p) 1 |
(b) p (x) = ax^{3} + 3x^{2} – 3 and q (x) = 2ax^{3} – 5x + a divided by (x – 4) leave the same remainder. Then, a = ….. | (q) -7 |
(c) If p (x) = 7x^{2} - 4x + c is completely divisible by (x - ), then c = ….. | (r) 0 |
(d) If q (x) = 2x^{3} + bx^{2} + 11x + b + 3 is divisible by (2x – 1), then b = ….. | (s) – 6 |
The correct answer is:
(a)-……., (b)-……., (c)-……., (d)-…….,